Treatment for Giant Aneurysms in the Cavernous Portion of the Internal Carotid Artery using Detachable Coils - Kai, Y. (Centauro S.r.l., 2000)
We report 7 patients with symptomatic giant aneurysms in the cavernous portion of the internal carotid artery (ICA) who were treated by trapping the ICA on either side of the aneurysmal orifice using detachable coils. In all 7 patients the ICA was sacrificed; 5 patients subsequently underwent bypass surgery (STA-MCA bypass, n = 4; high-flow bypass, n = 1), the other 2 patients did not. In 6 patients, there were no post-treatment embolic episodes; one patient who had been treated by proximal occlusion of the ICA developed transient ischemia due to an intra-aneurysmal thrombus. Cranial nerve palsies were markedly improved in all patients. ICA trapping using detachable coils was a highly successful treatment method in these patients. We found the detachable coils effective and easy to use in the trapping methods applied in this series of 7 patients.